Letrozole combined with low dose highly purified HMG for ovulation induction in clomiphene citrate-resistant infertile Chinese women with polycystic ovary syndrome: a prospective study. (3rd June 2017) - Zhao, Yue; Ruan, Xiangyan; Mueck, Alfred O.
Abstract: Background and aim : There are still open questions about ovulation induction in clomiphene citrate-(CC)-resistant infertile women. Especially little is known about efficacy and safety of letrozole (LTZ) combined with low-dose highly purified human menopausal gonadotropin (Hp-HMG) in women with polycystic ovary syndrome (PCOS). Methods : Prospective, single-arm single-center trial in 200 infertile PCOS patients refractory for at least three CC-treatment cycles. Women with hyperandrogenism took Diane-35 for at least 3 months. All patients got LTZ on day 3 for 5 d in combination with Hp-HMG, starting with 75 IU from cycle day 7 and maintained for up to 3 d. The maximum dose was 150 IU. Primary end-points were ongoing and clinical pregnancy rate, secondary end-points mono-follicular development, ovulation rate, OHSS, multiple pregnancy and early pregnancy loss. Major safety end-point was the incidence of adverse events. Results : Within 395 cycles the ongoing pregnancy rate was 28.24%, for cycles 35.23%, for patients 68%. The rate of ovulation per cycle was 97.7%, percentage of mono-follicular development 70.9%. No severe OHSS, multiple pregnancy, local or systemic side effects were seen. Conclusions : LTZ combined with low-dose Hp-HMG is an effective and safe choice for reducing hyperstimulation and increasing pregnancy rate in CC-resistant women with PCOS.